The genus Balbisia (Vivianiaceae, Geraniales) in Peru, Bolivia and northern Chile - Weigend, M. (Phytotaxa, 2011)
Four species of Balbisia (Vivianiaceae, Geraniales) are currently recognized for Peru, but these taxa are exceedingly difficult to key out with the available literature. The type specimens of some were lost in the Berlin fire and extant literature does not indicate any geographical differentiation between the taxa recognized. Based on extensive field studies in central and southern Peru, herbarium studies and observations in cultivation it is concluded that there really are only two, weakly differentiated and apparently allopatric taxa present in Peru, namely B. meyeniana and B. verticillata. Balbisia verticillata is widespread along the western flanks of the Andes from Lima to northern Moquegua and is replaced by B. meyeniana in northern Moquegua and Tacna. Balbisia weberbaueri, described from Arequipa, is just a seasonal variant of B. verticillata and is therefore here synonymized. Balbisia meyeniana and B. verticillata show no consistent differences in flower or fruit, but are quite readily separable: B. verticillata has narrowly elliptical-acuminate leaflets (often linear in dried material) with recurved margins and dense, sericeous to villous pubescence. Leaves are whitish in the living state and greyish in the herbarium. Balbisia meyeniana has flat, narrowly obovate-acuminate to elliptical leaflets, which are finely puberulent to subglabrous and often slightly glaucous (in the living state) or fresh green (in dried material). Both species apparently also occur in Bolivia, but neither has been so far reported from Chile. Conversely, the fourth species reported for Peru, B. peduncularis, is apparently not present there, but is endemic to Chile. A neotype is selected for Balbisia meyeniana, lectotypes are designated for B. peduncularis, B. integrifolia, B. verticillata, B. weberbaueri and Cruckshanksia cistiflora Hook.